The Search For Personal Identity In OscarWilde's The Importance Of Being Earnest (1895): An Individual Psychological Perspective - Admaja, Yuriike Wini, Drs. Muhammad Thoyibi, M.S, Titis Setyabudi, S.S M.Hum (2013)
The major problem of this study is to examine searching of personal identity is reflected in Oscar Wilde's The Important of Being Earnest drama. The objective of this study is to analyze the play based on the character of the major character and to analyze the play based on individual psychological perspective. The research is conducted by using qualitative method. The writer uses two data sources namely primary and secondary data source. The primary data is The Important of Being Earnest drama written by Oscar Wilde. The secondary data sources are the other sources related to the analysis like some books, author bibliography, articles, and references. The method of the data collection is library research. The technique of data analysis is descriptive analysis. Based on the research finding, it can be concluded that The Important of Being Earnest drama is Oscar Wilde wants to say that people tend to find out their own personal identity. Oscar wilde makes the major character not know his past and not know his true identity. Based on the individual psychological perspective, The Important of Being Earnest written by oscar wilde, illustrates individual psychological phenemenon in which the major character feels inferior for not knowing the real identity. In the story, oscar wilde makes Jack Worthing as a man who has no personal identity, Jack Worthing has been a double identity.